O pragnieniu życia wiecznego w świetle Ap 7,13-17 - Kotecki, Dariusz (2025)
The author of the article raises the question of the meaning of thirst in Rev 7:16 within the context of the pericope 7:13-17. The analysis is literary in character, focusing on the meaning of individual words, expressions, formulas, and images, while taking into account biblical and extra-biblical parallels within the broader contexts of the pericope itself (7:13-17), the entire Book of Revelation (where the terminology and context of 7:16 are closely related to 21:6 and 22:17), and the whole of Scripture. The author further assumes that the interpretive subject of the Apocalypse’s message is the liturgical assembly gathered for the Eucharist. The listening community, understood as a fellowship of redeemed sinners, receives in 7:13-17 an answer to three fundamental questions: (1) Who are the saved (7:13-14)? (2) What does it mean to be saved (7:15.17a)? (3) What are the fruits of salvation (7:16.17b)? On the basis of this analysis, the author concludes that 7:16 does not speak of physical thirst but of the thirst for salvation—for eternal life ("the springs of the water of life")—which later theology designates as the virtue of hope. The ways that lead to salvation, that is, to eternal life, consist in openness to the power and vitality that flow from the paschal mystery of Jesus and are realized in the sacramental life (baptism, Eucharist, cooperation with divine grace). This enables believers to endure all adversities and hardships arising from an environment hostile to Christians ("the great tribulation"). The entire narrative strategy of 7:13-17, not only of 7:16, in light of the question about salvation in 6:17, is directed toward awakening within the listening community the desire for eternal life.
Autor artykułu zadaje pytanie o znaczenie pragnienia w Ap 7,16 w kontekście perykopy 7,13–17. Przeprowadzona analiza jest typu literackiego. Polega ona na poszukiwaniu znaczenia poszcze-gólnych wyrazów, wyrażeń, formuł oraz całych obrazów z uwzględnieniem paralel biblijnych i pozabi-blijnych w ramach kontekstu, jaki stanowi perykopa 7,13–17, cała Apokalipsa (na polu terminologicz-nym i kontekstualnym 7,16 ściśle nawiązuje do 21,6 i 22,17) oraz cała Biblia. Autor przyjmuje także, że podmiotem interpretującym przesłanie Apokalipsy jest zgromadzenie liturgiczne zebrane na Eucha-rystii. Wspólnota słuchająca, która jest widziana jako wspólnota odkupionych grzeszników, otrzymuje w 7,13–17 odpowiedź na trzy zasadnicze pytania: (1) Kim są zbawieni (7,13–14)? (2) Co znaczy być zbawionym (7,15.17a)? (3) Jakie są owoce zbawienia (7,16.17b)? W wyniku analiz autor dochodzi do wniosku, że 7,16 nie mówi o pragnieniu fizycznym, ale o pragnieniu zbawienia – życia wiecznego („źró-dła wód życia”), które późniejsza teologia nazwie cnotą nadziei. Sposobami dojścia do zbawienia – życia wiecznego – są otwarcie się na moc i witalność, które płyną z misterium paschalnego Jezusa, a które realizuje się w życiu sakramentalnym (chrzest, Eucharystia, współpraca z łaską Bożą), co pozwala na zno-szenie wszelkich przeciwności, trudów, które płyną ze strony środowiska wrogiego chrześcijanom („wiel-ki ucisk”). Cała strategia narracyjna 7,13–17, nie tylko 7,16, w kontekście pytania o zbawienie w 6,17, zmierza do pobudzenia we wspólnocie słuchających pragnienia życia wiecznego.
Keywords: Eternal Life; great tribulation; Redemption; Salvation; thirst; water of life; pragnienie; woda życia; życie wieczne; odkupienie; Zbawienie; wielki ucisk